PENGEMBANGAN DISTRIBUSI PEMASARAN PRODUK GERABAH BAGI PENGRAJIN GERABAH DI DESA OUW KECAMATAN SAPARUA KABUPATEN MALUKU TENGAH - Audry Leiwakabessy; Ludwina Pormes (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2020)
This community service activity aims to help develop marketing distribution due to the fact that technically all pottery craftsmen in the village of Ouw have been able to innovate with existing handicraft businesses, but from the marketing side it is still very minimal due to a lack of knowledge and a lack of business networks formed with end sellers. The method used to be a solution to partner problem solving is training by providing materials that can be understood by pottery craftsmen in simple language. The result of the trainning activites is the pottery craftsmen can design a marketing distribution and will applied by promoting and building sales networks with souvenir shops and restaurants in the Ambon city. The conclusion of this community service activity is to provide an added value for business development and knowledge about the importance of building business networks with the assumption that if the production and marketing of pottery handicraft products goes well, it will have a possitive impact on the prosperity of them. Hopefully this community service activity can continue with a financial statement training and business development methods must be socialized by financial institutions or providers of business capital.